Brilliant ebook - Bendis, Brian Michael (Brilliant., 2022)
The first creator-owned book by Ultimate Spider-Man cocreators Brian Michael Bendis and Mark Bagley, Brilliant tells the story of a handful of college-age geniuses who challenge each other to solve the mystery of superpowers. Can the best and brightest change science fiction into science fact? And if so, how will the world at large react? Brilliant is a thriller of the highest order. It is a story of how true power can either destroy or protect the strongest of friendships. It is the story of how the world will react when our true potential is finally unlocked. Collecting Brilliant #1-#5.